Non-closure of the peritoneum during open appendicectomy decreases postoperative analgesia requirement - Modher Khalaf , Ahmed (Diyala Journal of Medicine, 2022)
Background: Acute appendicitis is considered the most common surgical emergency in both adults and children. Open rather than laparoscopic appendectomy is still the most commonly performed procedure. Objective: To assess the effect of non-closure of the peritoneum during appendectomy on postoperative pain and finally on the analgesia requirement. Patients and Methods: Two hundred patients underwent appendicectomy. The patients were divided into two equal groups; each had one hundred patients. Group 1 (control or closure Group) in which, the peritoneum is closed; in group 2 (study or non-closure Group), the peritoneum is left alone without closing it. Results: The mean pain score in the non-closure group was less compared to that in the closure group. A significant decrease in parenteral analgesia requirements was shown in the non-closure group compared to the closure group. Conclusion: Leaving the peritoneum not sutured during appendicectomy has a positive outcome on postoperative pain and decreases the requirement for analgesia.